Hydrogel modulate macrophages to promote myocardial repair after myocardial infarction - HUANG Huihui; CAI Yongxiang; DU Huan; CHENG Panke; LI Gang; TAO Jianhong (Yixue xinzhi zazhi)
Myocardial infarction (MI) is the necrosis of cardiomyocytes caused by insufficient coronary blood supply. The inflammatory response induced by necrotic cells alters the myocardial microenvironment and participates in the process of myocardial injury and repair. Macrophages are important executors of the inflammatory response and participate in the myocardial injury and healing process by secreting cytokines with different functions through different subtypes. Modulation of macrophage subtypes has emerged as a potential therapeutic strategy for myocardial repair. In recent years, hydrogel materials have been widely used in MI repair due to its good biocompatibility and functionalized modification ability. Functionalized hydrogels not only provide mechanical support, but also modulate macrophage subtypes, improve the immune microenvironment at the infarct site, and promote myocardial repair and regeneration. This article reviews the pivotal role of macrophages in MI and the current state of hydrogels in modulating macrophages to promote myocardial repair after MI.